The working stroke upon myosin–nucleotide complexes binding to actin - Steffen, Walter (National Academy of Sciences, 2003)
For many years, it has been known that myosin binds to actin tightly, but it had not been possible to devise a muscle fiber experiment to determine whether this binding energy is directly coupled to the working stroke of the actomyosin crossbridge cycle. Addressing the question at the single-molecule level with optical tweezers allows the problem to be resolved. We have compared the working stroke on the binding of four myosin complexes (myosin, myosin-ADP, myosin-pyrophosphate, and myosin-adenyl-5′yl imidodiphosphate) with that observed while hydrolyzing ATP. None of the four was observed to give a working stroke significantly different from zero. A working stroke (5.4 nm) was observed only with ATP, which indicates that the other states bind to actin in a rigor-like conformation and that myosin products (M.ADP.P(i)), the state that binds to actin during ATPase activity, binds in a different, prestroke conformation. We conclude that myosin, while dissociated from actin, must be able to take up at least two mechanical conformations and show that our results are consistent with these conformations corresponding to the two states characterized at high resolution, which are commonly referred to in terms of having open and closed nucleotide binding pockets.